Neonatal sepsis: Bacteriological profile,molecular detection and antimicrobial susceptibility test among pre-term pediatrics in Erbil city, Iraq - Abdul-Rahman, Sherko Muhammed; Khider, Adel Kamal (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Neonatal sepsis refers to infection occurring within the neonatal period, the first 28 days of life for a term baby, and up to 4 weeks beyond the expected date of delivery in a pre-term baby. This study was designed to determine the frequency of neonatal early onset sepsis and late onset sepsis in some hospitals in Erbil city. Methods: Out of 170 neonate samples from Neonatal Intensive Care Unit in Rapareen Pediatric Teaching Hospital and Maternity Obstetric Hospital randomly were studied through isolation and identification of causative bacteria using the traditional approach, VITEK 2 compact system, molecular detection using PCR technique, moreover, C-reactive protein and white blood cell count detected as biomarker assay. The isolated bacteria tested against some widely used antibiotics. Results: The sepsis was confirmed in 54 (31.76%) patients of total neonates with suspected cases of sepsis by clinical signs and symptoms. EOS was 42 (77.77%) were detected, and late onset sepsis was 12 (22.23%). Identification of the isolated bacteria by the traditional method, and VITEK 2 compact system were performed. In addition, molecular detection via the PCR system through the detection of the specific genes was performed. Antimicrobial Susceptibility test indicated that most of the isolated bacteria were developed resistant to the most widely used antimicrobials. Conclusion: Our study showed a high incidence of neonatal early onset sepsis more than late onset sepsis, mostly associated with Gram-negative bacteria than Gram-positive bacteria.